1972
DOI: 10.1113/jphysiol.1972.sp009979
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular and respiratory responses to changes in central command during isometric exercise at constant muscle tension

Abstract: SUMMARY1. Experiments were designed to show whether elements of the command descending from higher centres to exercising muscles provide an input for cardiovascular and respiratory control. Vibration, known to be a powerful stimulus to the primary afferents from muscle spindles, was applied to the biceps tendon of human subjects performing sustained isometric contractions with the biceps or the triceps muscle. When the biceps was contracting this activation of muscle spindle primary afferents in it provided an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
392
1
13

Year Published

1987
1987
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 596 publications
(419 citation statements)
references
References 11 publications
13
392
1
13
Order By: Relevance
“…In the present study, we observed a significant decrease in MEP from IE 1st to IE 2nd . Therefore, the findings in the present study not only support the above concept (Amman et al 2013) but also suggest that effort-mediated ventilatory response during fatiguing IE cannot be explained by the conventional framework of central command that drives breathing via neural mechanisms consisting of parallel activation of motor and respiratory centers (Goodwin et al 1972;Heigenhauser et al 1983;Krogh and Lindhard 1913;Marcora et al 2008). Recent studies (Decety et al 1991;Thornton et al 2001;Williamson et al 2002Williamson et al , 2006Yunoki et al 2009) using a cognitive approach to dissociate peripheral neural signals from central command have suggested that central command-mediated response does not necessarily require parallel activation of central motor command.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In the present study, we observed a significant decrease in MEP from IE 1st to IE 2nd . Therefore, the findings in the present study not only support the above concept (Amman et al 2013) but also suggest that effort-mediated ventilatory response during fatiguing IE cannot be explained by the conventional framework of central command that drives breathing via neural mechanisms consisting of parallel activation of motor and respiratory centers (Goodwin et al 1972;Heigenhauser et al 1983;Krogh and Lindhard 1913;Marcora et al 2008). Recent studies (Decety et al 1991;Thornton et al 2001;Williamson et al 2002Williamson et al , 2006Yunoki et al 2009) using a cognitive approach to dissociate peripheral neural signals from central command have suggested that central command-mediated response does not necessarily require parallel activation of central motor command.…”
Section: Discussionsupporting
confidence: 86%
“…Effort-mediated ventilatory response during exercise is generally explained by a feedforward mechanism involving activation of the cardiorespiratory center, which is induced, in parallel, by activation of the motor cortex (central motor command) (Goodwin et al 1972;Heigenhauser et al 1983;Krogh and Lindhard 1913;Marcora et al 2008). However, it has been confirmed that during IE performed after muscle glycogen reduction, integrated electromyogram (iEMG) activity recorded in exercising muscle, which reflects central motor command (Amann et al 2006;Amann and Dempsey 2008), does not increase while ventilation is elevated (Osborne and Schneider 2006;Perrey et al 2003;Yamanaka et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…However, in experimental models in which one of the components is increased or decreased, the other may produce a near appropriate cardiovascular response. For example, some studies have emphasized the importance of the central neural component (Freyschuss, 1970;Goodwin, McCloskey & Mitchell, 1972;Schibye, Mitchell, Payne & Saltin, 1981;Secher, 1985;Leonard et al 1985) and others have emphasized the importance of the reflex neural component (Alam & Smirk, 1937;Hultgren & Sj6holm, 1982). Also animal studies have shown that cardiovascular responses similar to those occurring during exercise can be produced by either central or reflex neural mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Central command emanates from the rostral brain and radiates to neural circuits in the brainstem, thereby causing parallel activation of motor and sympathetic neurons 1) . The muscle based reflex, termed 'exercise pressor reflex' (EPR) 2) , is evoked as thin fiber muscle afferents (groups III and IV) are stimulated by mechanical deformation of the afferents' receptive fields, as well as by metabolic byproducts during exercise (muscle mechano-and metaboreflexes, respectively).…”
Section: Introductionmentioning
confidence: 99%